Hej!
Podpunkt a)
[tex]3(5x-8z-2)=\\\\=3\cdot5x-3\cdot8z-3\cdot2=\\\\=\boxed{15x-24z-6}[/tex]
Podpunkt b)
[tex]-8(7n+9p+t)=\\\\=-8\cdot7n-8\cdot9p-8\cdot t=\\\\=\boxed{-56n-72p-8t}[/tex]
Podpunkt c)
[tex]3(b-5a)-2(3b+a)=\\\\=3\cdot b-3\cdot5a-2\cdot3b-2\cdot a=\\\\=3b-15a-6b-2a=\\\\=\boxed{-17a-3b}[/tex]
Podpunkt d)
[tex]5(2x+3y)-(x-2y)=\\\\=5\cdot2x+5\cdot3y-x+2y=\\\\=10x+15y-x+2y=\\\\=\boxed{9x+17y}[/tex]
Uwaga! Minus przed nawiasem zmienia znaki każdego czynnika w nawiasie na przeciwne.
Podpunkt e)
[tex]4(\frac{x}{4}+\frac{y}{4})-5(\frac{3x}{5}-\frac{7y}{5})=\\\\=\frac{4x}{4}+\frac{4y}{4}-\frac{15x}{5}+\frac{35y}{5}=\\\\=x+y-3x+5y=\\\\=\boxed{-2x+6y}[/tex]
Podpunkt f)
[tex]-6(\frac{3x}{6}-\frac{2y}{6})+\frac{2}{3}(\frac{3x}{2}-6y)=\\\\=-\frac{18x}{6}+\frac{12y}{6}+\frac{2x}{2}-\frac{12y}{3}=\\\\=-3x+2y+x-4y=\\\\=\boxed{-2x-2y}[/tex]
Pozdrawiam! ~ JulkaOdMatmy